2003
DOI: 10.1197/aemj.10.8.842
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Communication: Assessment‐oriented Oral Case Presentation

Abstract: AO oral case presentation may provide a means for emergency medicine residents to "get to the point" and to communicate effectively and efficiently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 6 publications
(3 reference statements)
0
6
0
2
Order By: Relevance
“…In the case of an EM resident presenting a patient in the assessment-oriented way, in which the assessment precedes the presentation, confirmatory data may be highlighted to reinforce the assessment, whereas nonconfirmatory data (that may or may not have been asked for) may be omitted. 19 However, the presence of multiple providers may help prevent confirmation bias because one provider may get a critical bit of information that differs from the first providers', and he or she accordingly changes the plan of care. When a medical student spends an hour taking an exhaustive history and physical examination, that student's lack of direction (and lack of knowledge of heuristics) ultimately can lead to pertinent information being found that may not have been found in a briefer encounter.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of an EM resident presenting a patient in the assessment-oriented way, in which the assessment precedes the presentation, confirmatory data may be highlighted to reinforce the assessment, whereas nonconfirmatory data (that may or may not have been asked for) may be omitted. 19 However, the presence of multiple providers may help prevent confirmation bias because one provider may get a critical bit of information that differs from the first providers', and he or she accordingly changes the plan of care. When a medical student spends an hour taking an exhaustive history and physical examination, that student's lack of direction (and lack of knowledge of heuristics) ultimately can lead to pertinent information being found that may not have been found in a briefer encounter.…”
Section: Discussionmentioning
confidence: 99%
“…This checklist may be adapted by researchers in the same scope of study, and not limited to those from United States of America only, but also to all researchers from all over the world, particularly researchers who are interested in the structure of OCPs by medical students. Maddow et al (2003) investigated the effectiveness of assessment-oriented (AO) OCP as a model of inter-physician communication. They argued a traditional format of OCP consists of seven moves which are chief complaint, history of present illness, past medical, social and family histories, physical examination, ancillary data, assessment and plan.…”
Section: Rhetorical Moves In Ocpsmentioning
confidence: 99%
“…Here, she stated that it is a "medicine's principal way of applying its abstract knowledge to the care of the individual patient" (p.47). Once the physicians receive stories from their patients, they will clerk the case into a general template called case report, which constitutes a chief complaint, history of present illness, past medical history, personal and social history, family history, drug history, physical examination, laboratory and diagnostic findings data, summary statement, assessment, plan and medical records after discharge (Dell et al, 2012;Hung et al, 2012;Anspach, 1989;Maddow et al, 2003;Davenport et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20][21] A few publications, however, have been dedicated to teaching in the ED. 7,[22][23][24][25] The ED seems to be fertile training ground for educating medical students. Many of the teaching techniques from other settings can be adapted to enhance clinical teaching in the ED.…”
Section: Opportunities For Teaching In the Edmentioning
confidence: 99%
“…25 Maddow et al describe the use of an assessmentoriented style of oral case presentations by EM residents. This style differs from the traditional case presentation model previously described.…”
Section: Student Case Presentationsmentioning
confidence: 99%